Jezikovni priročniki in novi mediji - Krek, Simon (Jezik in slovstvo, 2003)
The article deals with reference books and other sources of data about Slovenian language found in digital form. It begins with dictionaries as classic reference books in various computer environments, followed by morphological lexicons and language corpora as the new types of reference tools and finaly language proofing tools found in text processors, translation software and speech technologies. The article ends with a short assessment of current situation and prediction for future development.
Keywords: Slovene; slovenščina; Corpus linguistics; korpusno jezikoslovje; Language technology; jezikovne tehnologije